An Interest Rate Peg Might Be Better than You Think - Markus Hörmann; Andreas Schabert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
Active interest rate policy is frequently recommended based on its merits in reducing macroeconomic volatility and being a simple and transparent policy device. In a standard New Keynesian model, we show that an even simpler policy, namely an interest rate peg, can be welfare enhancing: The minimum state variable solution and an autoregessive solution under a peg can lead to lower welfare losses than the unique solution under an active interest rate rule. Given that a peg is usually blamed to facilitate endogenous fluctuations, we further show that a peg can be implemented in a way that ensures equilibrium determinacy.
Keywords: E52; E51; E32; 330; Interest rate rules; welfare losses; equilibrium determinacy; fundamental solutions; Zinspolitik; Regelgebundene Politik; Wirtschaftspolitische Wirkungsanalyse; Wohlfahrtseffekt; Ungleichgewichtstheorie; Theorie